Using print narrative to address mental illness stigma. - Liao, Jun Qi. (2011)
Mental health stigma in Singapore is a pressing issue. Understanding the factors that would affect stigma reduction is a matter of practical and theoretical significance. This study measures the effectiveness of narratives in print brochures as a mental health stigma reduction strategy. This study also looks at how manipulating source type (doctor vs. patient), and stigma attributions of stability (lowly unstable vs. highly unstable) and controllability (biological vs. psychosocial) of the illness within these narratives affect the effectiveness of print brochures. This experiment revealed that print narratives in brochures were effective in changing participants’ attitudes towards people with mental illness, regardless of conditions. In addition, the doctor narrative was perceived to have higher source expertise while the patient narrative was perceived to have higher source trustworthiness. Higher source expertise was found to be more effective in changing attitudes when participants had low issue involvement with mental illness and negative pre-attitudes towards mental illness. In contrast, higher source trustworthiness was more effective in changing attitudes when participants had high issue involvement and positive pre-attitudes towards mental illness.